Arabidopsis requires polyunsaturated lipids for low-temperature survival. - Miquel, M (1993)
Mutants of Arabidopsis that contain reduced levels of polyunsaturated fatty acids showed growth characteristics at 22 degrees C that were very similar to wild type. By contrast, at 12 degrees C, the mutants failed to undergo stem elongation during reproductive growth although they produced normal flowers and fertile seeds. After transfer to 6 degrees C, rosette leaves of the mutants gradually died, and the plants were inviable. These different responses of the mutant plants at 12 degrees C and 6 degrees C suggest that distinct functions may be affected at these two temperatures. The gradual development of symptoms at 6 degrees C and other lines of evidence argue against a general collapse of membrane integrity as the cause of the lethal phenotype. Rather, they indicate that the decrease in polyunsaturated membrane lipids may initially have relatively limited effects in disrupting cellular function.